2021
DOI: 10.1371/journal.pone.0252949
|View full text |Cite
|
Sign up to set email alerts
|

DRUL for school: Opening Pre-K with safe, simple, sensitive saliva testing for SARS-CoV-2

Abstract: To address the need for simple, safe, sensitive, and scalable SARS-CoV-2 tests, we validated and implemented a PCR test that uses a saliva collection kit use at home. Individuals self-collected 300 μl saliva in vials containing Darnell Rockefeller University Laboratory (DRUL) buffer and extracted RNA was assayed by RT-PCR (the DRUL saliva assay). The limit of detection was confirmed to be 1 viral copy/μl in 20 of 20 replicate extractions. Viral RNA was stable in DRUL buffer at room temperature up to seven days… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In contrast, saliva sampling is too easy and can be done by the patient providing solid results [ 40 ]. Recently, a study validated a safe and sensitive SARS-CoV-2 detection by RT-qPCR using saliva, which they called DRUL saliva test, with limit of detection similar to nasopharyngeal swab samples in order to implement the method for “back to work/school [ 41 ].…”
Section: Influencing Factors On Sars-cov-2 Detectionmentioning
confidence: 99%
“…In contrast, saliva sampling is too easy and can be done by the patient providing solid results [ 40 ]. Recently, a study validated a safe and sensitive SARS-CoV-2 detection by RT-qPCR using saliva, which they called DRUL saliva test, with limit of detection similar to nasopharyngeal swab samples in order to implement the method for “back to work/school [ 41 ].…”
Section: Influencing Factors On Sars-cov-2 Detectionmentioning
confidence: 99%
“…Previous work has shown that nucleic acids are recoverable from biological liquids, including saliva, dried on specialized paper filters and stored at −70°C for up to 14 months and then one week at ambient temperature (8). Saliva is easy to sample and widely used for clinical SARS-CoV-2 real-time quantitative qPCR assays (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that nucleic acids, DNA and RNA, are recoverable from biological liquids dried on specialized paper filters and stored in freezers [8]. Saliva is easy to sample and widely used for clinical SARS-CoV-2 real-time quantitative (RT-q) PCR assays [9][10][11].…”
Section: Introductionmentioning
confidence: 99%